Nutritional conditions indicators in Polonoroeste Area: II - Anthropometric study, 1983 - Yokoo, E.M.; Guimarães, L.V.; Silva, R.A.P.R. da; Spinelli, M.A. dos Santos; Albuquerque, M.C.W. (Revista do Instituto de Medicina Tropical de São Paulo, 1988)
A study of the nutritional state through anthropometry was made in order to describe the prevalence and the protein-energetic undernutrition form within six cities of Polonoroeste/MT area. The anthropometric test was done over a group of 573 children from 3 to 72 months old, of both sex. For the manipulation of the collected data, the classification proposed by GOMEZ and WATERLOW was used, being still done the distribution of weight and height in percentage ranges. Following GOMEZ classification the undernutrition prevalence met was of 51%, being that the highest percentage found was in the city of Jauru (79.2%) and the lowest in Araputanga city (31.3%). As for the undernutrition form, the highest prevalence was the past undernutrition showing an accentuated compromise of the height confirmed through the percentage distribution.